Sexual satisfaction among involuntarily childless women: A cross-cultural study in Italy and Brazil. Issue 1 (2nd January 2018) - Gremigni, Paola; Casu, Giulia; Mantoani Zaia, Victor; Viana Heleno, Maria Geralda; Conversano, Ciro; Barbosa, Caio Parente
ABSTRACT: Infertility has been negatively associated with sexual satisfaction. This study aimed to estimate the relation of infertility to sexual satisfaction from a cross-cultural perspective, comparing Italian and Brazilian women. Between June 2012 and January 2013, 528 women seeking assisted reproduction technology (ART) treatment in Italy (39%) or Brazil (61%) completed self-reports of sexual satisfaction (ISS) and infertility-related stress in the marital domain (IRS). IRS was the same across countries. ISS differed, with 34.31% of the Italians and 43.52% of the Brazilians being sexually dissatisfied at a clinical level (ISS score >30). Multiple logistic regression models showed that being sexually dissatisfied at a clinical level was associated with lower education and higher IRS among Italian women, regardless of having a diagnosed cause of infertility. It was instead associated with higher IRS only among the Brazilian women who had a diagnosed cause of infertility. These findings suggest that, regardless of nationality, sexual satisfaction and infertility-related stress need to be addressed in the treatment of infertile women turning to ART. However, as factors associated with these dimensions vary across countries, interventions to promote sexual satisfaction among infertile women should be adapted to their specific socio-cultural context.